2002
DOI: 10.1021/jf0114334
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Gel Properties of Dried Egg White by Modification with Galactomannan through the Maillard Reaction

Abstract: The effects of Maillard reaction on gel properties of dried egg white (DEW) with galactomannan (GM) were investigated. Maillard-reacted DEW (MDEW) was prepared by dry-heating a mixture with a weight ratio of 1:4 of GM to DEW at 60 degrees C and 65% relative humidity. The modification of amino groups and polymerization of DEW proteins dry-heated with GM proceeded with increasing the dry-heating time. The covalent attachment of GM to DEW was confirmed from SDS-PAGE analysis. Gel strength and water-holding capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 40 publications
2
38
1
Order By: Relevance
“…Recent results on dry heating of EA for 7 days at 60 • C found SDS-PAGE patterns to be unchanged throughout the period. 48 The mechanisms in protein aggregation during dry-heating is yet not fully understood, and especially the nature of the protein interactions as function of dry heat temperature needs further study. Figure 4A shows that the WHC of the gels is ∼750 g kg −1 for raw EA, which subsequently decreases to 580 g kg −1 during bulk storage and centrifugation and then steadily increases to 780 g kg −1 in gels of the final product.…”
Section: Resultsmentioning
confidence: 99%
“…Recent results on dry heating of EA for 7 days at 60 • C found SDS-PAGE patterns to be unchanged throughout the period. 48 The mechanisms in protein aggregation during dry-heating is yet not fully understood, and especially the nature of the protein interactions as function of dry heat temperature needs further study. Figure 4A shows that the WHC of the gels is ∼750 g kg −1 for raw EA, which subsequently decreases to 580 g kg −1 during bulk storage and centrifugation and then steadily increases to 780 g kg −1 in gels of the final product.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] In addition to providing a dramatic improvement in the emulsifying properties of proteins, this approach has improved their solubility and gelling properties, enhanced their antioxidative effects, and broadened their bactericidal effects. [7][8][9][10] Therefore, protein-polysaccharide conjugates, which are natural, non-toxic, and have improved functional properties, have significant potential for use by the food and health industries. 11) Bovine serum albumin (BSA) is a major globular protein of bovine blood plasma.…”
mentioning
confidence: 99%
“…[18][19][20][21] Many studies have been carried out on the functional properties of protein-polysaccharide conjugates. [4][5][6][7][8][9][10][11] However, much less work has been reported on the interaction between a protein and polysaccharide. 22,23) In particular, the molecular properties of protein-polysaccharide conjugates formed via specific covalent bonding, as occurs with the Maillard reaction, have not been characterized in detail.…”
mentioning
confidence: 99%
“…Protein-polysaccharide conjugates have also been explored for their gelling and foaming properties compared to native proteins [16,60,61]. Matsudomi et al [60] compared the gelling properties of egg white-galactomannan conjugates with egg white protein alone and showed an increase of gel strength and water retention capacity.…”
Section: Gelling and Foaming Propertiesmentioning
confidence: 99%
“…Matsudomi et al [60] compared the gelling properties of egg white-galactomannan conjugates with egg white protein alone and showed an increase of gel strength and water retention capacity. More recently, Spotti et al [16] reported that WPI-DX conjugates significantly enhanced the mechanical properties of the gels, which could be subjected to as high as 80% deformation in a uniaxial compression test without fracture, far higher than the gel prepared by non/unconjugated WPI-DX mixture [16].…”
Section: Gelling and Foaming Propertiesmentioning
confidence: 99%